PAHs in decaying Quercus ilex leaf litter: Mutual effects on litter decomposition and PAH dynamics - De Nicola, F; Baldantoni, D; Alfani, a (Chemosphere, 2014)
The investigation of the relationships between litter decomposition and polycyclic aromatic hydrocarbons (PAHs) is important to shed light not only on the effects of these pollutants on fundamental ecosystem processes, such as litter decomposition, but also on the degradation of these pollutants by soil microbial community. This allows to understand the effect of atmospheric PAH contamination on soil PAH content via litterfall. At this aim, we studied mass and PAH dynamics of Quercus ilex leaf litters collected from urban, industrial and remote sites, incubated in mesocosms under controlled conditions for 361d. The results highlighted a litter decomposition rate of leaves sampled in urban>industrial>remote sites; the faster decomposition of litter of the urban site is also related to the low C/N ratio of the leaves. The PAHs showed concentrations at the beginning of the incubation of 887, 650 and 143ngg−1d.w., respectively in leaf litters from urban, industrial and remote sites. The PAHs in litter decreased along the time, with the same trend observed for mass litter, showing the highest decrease at 361d for the urban leaf litter. Anyway, PAH dynamics in all the litters exhibited two phases of loss, separated by a PAH increase observed at 246d and mainly linked to benzo[e]pyrene.
Keywords: C/N ratio; decomposition; Holm oak; Litter bags; Litter PAH contamination

Litter decomposition in Mediterranean ecosystems: Modelling the controlling role of climatic conditions and litter quality - Incerti, Guido; Bonanomi, Giuliano; Giannino, Francesco; Rutigliano, Flora Angela; Piermatteo, Daniela; Castaldi, Simona; De Marco, Anna; Fierro, Angelo; Fioretto, Antonietta; Maggi, Oriana; Papa, Stefania; Persiani, Anna Maria; et al. (Applied Soil Ecology, 2011)
A new process-based model of litter decomposition, characterized by detailed climatic data input and simple litter quality parameters, is proposed. Compared to existing litter carbon models, speciﬁc implementations for temperature and moisture limiting effects have been adopted. The model is capable to represent decomposition processes in Mediterranean ecosystems, with summer drought slowing down, even at optimal temperatures, the litter decay rates of sclerophyll plants whose leaf masses are rich in structural compounds and low in N content. The model was calibrated by a best ﬁtting procedure of two different datasets. First, unpublished results of litterbag experiments on leaf litter of 9 Mediterranean species, decomposing under controlled and not limiting temperature and water conditions, have been used to estimate the decay rate dependency from litter quality that was deﬁned by only three initial C pools (labile, stable and recalcitrant compounds) instead of traditional N-based indices. Second, a set of published data from three medium-term ﬁeld experiments on a single species, Phillyrea angustifolia, decomposing under different climatic conditions, have been used to estimate the limiting effects of temperature and moisture. The model was then validated against published data on seven other species and showed a correct reproduction ofthemajor patterns of littermass loss during decomposition processes of other seven different Mediterranean species. The model simulations, satisfactory for different litter types under a wide range of climatic conditions, suggest that factors which were not taken into account, such as initial litter N contents, microclimatic variations related to stand structure, soil chemistry and texture, and microbial communities, are not very signiﬁcant for assessing decomposition dynamics in Mediterranean ecosystems. The minimal requirements of input data, the simple structure, and the easiness of parameterisation make our model, among the many other available litter carbon models, an attractive alternative for different research purposes, at least for Mediterranean ecosystems.
Keywords: C model; C/N ratio; Initial C pools; process-based model; Semi-arid ecosystems; System dynamics

Litter dynamics in post-fire successional forests of Quercus ilex - FERRAN, A.; Vallejo, V. R. (Plant Ecology, 1992)
Forest floor regeneration after fire in a holm oak forest was studied in a chronosequence in Catalonia (NE Spain). The sampled area represented situations of high fire disturbance because of the frequency of wildfires and the high impact of erosive processes. Forest floor bulk samples from the L, F and H layers were taken in 5 burned plots, aging from 0 to 35 years. They were analyzed for dry standing weight, and organic carbon and N content. Plant cover reached almost 100°o two years after the fire. During the first 20 years, shrubs and herbs had the highest surface covering, and thereafter, holm oaks became dominant. Holm oak litterfall stabilized by the fourth year after burning. The major shrub species which were present in the chronosequence had two different patterns with respect to nitrogen: 1) a low litter C/N ratio (i.e. nitrogen fixing species); 2) a high litter C/N ratio. The litter decay coefficients were relatively high, allowing for a rapid structuration and formation of the L and F layers after the fire. Indeed, 95 ° o of the maximum steady standing weight accumulates in 8-9 years. The pattern of cover in the different strata influenced the lateral distribution and variable accumulation of the forest floor layers and determined different turnover rates.
Keywords: C/N ratio; Decay coefficient; Holm oak; mediterranean forest; plant regeneration